The Origins of the Ancient Philosophy - Jankauskas, Skirmantas (Problemos, 1987)
The ancient philosophy is considered as the form of thinking of the specific man, namely, of the wise-viewer. The practical position of the man has shaped itself on the base of the ideological opposition between a free citizen and a slave, and has meant the negation of the practical interests. This has enabled the ancient man to view the outer world disinterestedly. The value of beauty conformed with this particular outlook. It made the practical position of the ancient man concrete and was the impetus to the kind of activity as a result of which the first form of theoretical thinking – the ancient philosophy – was born.